إعداد برنامج تربية صحية لتنمية الوعي الصحي عند مرض ىسرطان القولون. - مصطفى, اميرة حسناء (كلية العلوم الاجتماعية, 2020)
الملخص: يهدف البحث الحالي إلى إعداد برنامج التربية الصحية لتنمية الوعي الصحي عند مرضى سرطان القولون، فتبنينا مسار ا توجيهيا تطبيق البرنامج ّ له تطبيق استبيان لتقيم مدى الوعي الصحي عند المريض ثم ّ للحالة أو د المريض بمعلومات حول النظام الغذائي الصحي الخاص ّ ن من مجموعة من الجلسات التي تزو ّ والذي يتكو بمرضى سرطان القولون، والتربية البدنية، و اقتراحات لتجاوز اضطرابات النوم، العالجات البديلة، والتدريب ر الوعي الصحي لدى المريض ّ إعادة تمرير نفس االستبيان وهذا قصد تقييم مدى تطو ّ على االسترخاء، ثم عرض البرنامج على عدد من المختصين في علم النفس وأخذت آ ارئهم ّ وفعالية البرنامج. كما تم بعين االعتبار اعداد الصيغة النهائية للبرنامج بما ّ ، وبعد ذلك تم بناؤه ّ يتوافق مع العينة التي تم عليها. الكلمات المفتاحية: التربية، الصحة، الوعي، السرطان، سرطان القولون. Abstract : The current research aims to build a health education program to develop health awareness in patients with colon cancer, so we adopted a course of guidance for these cases, firstly applying a questionnaire to assess the extent of health awareness on our patients, then implementing the program, which consists of a set of sessions that provide the patient with information about a healthy diet for cancer patients Colon, physical education, suggestions to bypass sleep disorders, alternative therapies, and relaxation training, then re-pass the same questionnaire in order to assess the extent to which health awareness has evolved in the patient and effectiveness of the program. The program was also presented to a number of psychologists and their opinions were taken, after which the final version of the program was prepared in accordance with the sample that was built on it. Key words: education, health, awareness, cancer, colon cancer.
Keywords: تنمية الوعي الصحي ،مرض ىسرطان القولون.